A Novel H∞ Robust Control Strategy for Voltage Source Inverter in Microgrid - Shi, Hongtao; zhang, Jie; Zhou, Jian; Li, Yifan; Jiang, Zhongnan (Frontiers in Energy Research, 2021)
The voltage control performance of the voltage source inverter (VSI) in a microgrid may change under different load conditions. However, in the case of traditional control strategies, the robustness of VSI is insufficient. In response to the above problems, a novel robust control scheme for VSI in the microgrid based on H∞ hybrid sensitivity is proposed in this study. The grid-side interference during the VSI operation is taken as the variable, and the sensitivity function is designed to build a H∞ robust voltage controller for VSI. In addition, an adaptive virtual impedance group is designed to further improve the voltage control robustness under a variety of operation conditions. Finally, comparative simulation experiments are carried out to verify the anti-interference ability of the proposed control strategy under different working conditions.